The pattern of community empowerment after complete systematic land registry (PTSL) - Hadi Arnowo (Monas: Jurnal Inovasi Aparatur, 2019)
This paper aims to determine the appropriate community empowerment strategy after the achievement of the activities of Complete Systematic Land Registry (PTSL). This research was conducted using descriptive method that explained the pattern of community empowerment that could be done after the activities of PTSL. The government had increased the target of land certificate issuance through PTSL. Communities that had received the certificates were still faced with the problem of limited business. Community empowerment efforts needed to be done through capital access assistance, technical and managerial guidance and marketing.. Land certificates that had been accepted by the community could be used for access to capital through various business schemes. Technical and managerial guidance was provided by the relevant technical institutions. While product marketing was assisted by local government and related institutions. Broadly speaking, the typology of the recipient community of the PTSL certificate that needed to be empowered was the urban community, the rural area and the coastal area. The pattern of community empowerment in each region should have considered the business potential, knowledge and skills of the community as well as the marketing network. Community participation should have be involved in every stage of community empowerment activities.